Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1103/physrevb.93.195145
|View full text |Cite
|
Sign up to set email alerts
|

Interaction-driven Lifshitz transition with dipolar fermions in optical lattices

Abstract: Anisotropic dipole-dipole interactions between ultracold dipolar fermions break the symmetry of the Fermi surface and thereby deform it. Here we demonstrate that such a Fermi surface deformation induces a topological phase transition -so-called Lifshitz transition -in the regime accessible to present-day experiments. We describe the impact of the Lifshitz transition on observable quantities such as the Fermi surface topology, the density-density correlation function, and the excitation spectrum of the system. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 119 publications
(138 reference statements)
0
6
0
Order By: Relevance
“…The ground-state [39,40] and the dynamic properties of such systems have been systematically investigated theoretically and numerically in the collisionless regime [41][42][43], in the hydrodynamic regime [44,45], as well as in the whole collisional range from one limiting case to the other [46,47]. The FS deformation was also recently theoretically studied in mixtures of dipolar and non-dipolar fermions [48], as well as in the presence of a weak lattice confinement [49].…”
Section: Introductionmentioning
confidence: 99%
“…The ground-state [39,40] and the dynamic properties of such systems have been systematically investigated theoretically and numerically in the collisionless regime [41][42][43], in the hydrodynamic regime [44,45], as well as in the whole collisional range from one limiting case to the other [46,47]. The FS deformation was also recently theoretically studied in mixtures of dipolar and non-dipolar fermions [48], as well as in the presence of a weak lattice confinement [49].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, p-wave superfluidity may arise. The interplay between lattice and dipole-induced Fermi surface deformation has also been predicted to yield a topological phase transition, of a Lifshiftz type [731]. Of even larger interest has been a case recovering a situation closer to the bosonic model, with (effective) spin-1/2 fermions as for the conventional Hubbard model; see Eq.…”
Section: Extended Hubbard Hamiltonian and Consequencesmentioning
confidence: 99%
“…( 77) cancels, only retaining the tunnelling and NNI terms. Theoretically, this case is also of interest, yet turns out to be more complicated to treat than the boson one [14,144,[726][727][728][729][730][731]. Few studies have shown that various kinds of charge-density-wave and supersolid phases also forms in dipolar fermions lattice systems in 2D [726][727][728][729] and 3D [730].…”
Section: Extended Hubbard Hamiltonian and Consequencesmentioning
confidence: 99%
“…For spinless fermions, a similar expression equation ( 77) can also be derived, yet because of the Pauli exclusion principle, the second and fourth terms of the sum in equation ( 77) cancels, only retaining the tunnelling and NNI terms. Theoretically, this case is also of interest, yet turns out to be more complicated to treat than the boson one [13,146,[739][740][741][742][743][744][745]. Few studies have shown that various kinds of charge-density-wave and SSPs also forms in dipolar fermions lattice systems in 2D [739][740][741][742]744] and 3D [743].…”
Section: Extended Hubbard Hamiltonian and Consequencesmentioning
confidence: 99%